2009
DOI: 10.1007/s10530-009-9574-5
|View full text |Cite
|
Sign up to set email alerts
|

Alien pollen grains interfere with the reproductive success of native congener

Abstract: The effects of invasive species on native species comprise important conservation issues. Determining the mechanisms by which invasives exclude natives is indispensable to efficiently control their impact, but most invasives remain poorly studied. The purpose of this study was to elucidate potentially important but neglected mechanisms, reproductive interference, in wild Taraxacum systems, in which invasive Taraxacum officinale has displaced its native congener T. japonicum in Japan. Hand-pollination of mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(99 citation statements)
references
References 51 publications
2
96
0
1
Order By: Relevance
“…For example, the native dandelion in Japan has been displaced by the alien congener, especially in urban areas. Our previous reports have described that the reproductive interference played a crucial role in displacement [6,7]. Similarly, reproductive interference has been suspected as an important factor of the extinction of the Japanese cocklebur, Xanthium japonica, in western Japan [8].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, the native dandelion in Japan has been displaced by the alien congener, especially in urban areas. Our previous reports have described that the reproductive interference played a crucial role in displacement [6,7]. Similarly, reproductive interference has been suspected as an important factor of the extinction of the Japanese cocklebur, Xanthium japonica, in western Japan [8].…”
Section: Introductionmentioning
confidence: 91%
“…To assess the true universality of the phenomenon, it is necessary to consider publication bias [12], which occurs because researchers 2 ISRN Botany might not seek to report negative results and editors might not desire to accept such reports for publication. In fact, most published studies of reproductive interference have reported positive results only ( [6,7,13], but see [14]). To discuss the universality of the reproductive interference fairly, it is necessary to review not only the detection of the reproductive interference but also reports of its absence.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive interference refers to any interspecific interaction that engenders the loss of the reproductive success in either or both interacting species. In plants, for example, heterospecific pollens have been known to interfere with ordinary insemination by conspecific pollens [10][11][12]. This is an extremely common mechanism affecting reproductive interference in plants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is much evidence that crops and other domesticated plants can hybridize with their wild relatives while still in cultivation (Ellstrand, 2003). Reproductive interference, which is the depression of fitness by interspecific pollination www.intechopen.com Introgression and Long-Term Naturalization of Archaeophytes into Native Plants-Underestimated Risk of Hybrids 49 interactions such as competition for limited pollinators and pollen loss by interspecific pollen transfer, has recently been recognized (Matsumoto et al, 2010;Takakura et al, 2011). In both phenomena, negative effects could become evident on the human timescale if a plant was cultivated extensively, such as agricultural crops.…”
Section: Negative Effect Of Archaeophytes Through Hybridizationmentioning
confidence: 99%